Wood Decaying Fungi of Teak from Madhya Pradesh, India - Tiwari, C. K.; Harsh, N. S. K. (Indian Forester, 2005)
Seventeen wood decaying fungi occurring on teak in Madhya Pradesh are reported. Eleven of these fungi are reported as new records on teak and six are being reported as new on teak from Madhya Pradesh. There are two root rot fungi on living trees of teak, Aurificarea shoreae and Ganoderma lucidum.